Systemic Inflammasome Biomarkers as Predictors of Diabetic Retinopathy Progression: Evidence from a Pilot Study - Charisse Y.-J. Kuo; Ilva D. Rupenthal; Michael Booth; Rinki Murphy; Odunayo O. Mugisho (MDPI AG, 2023)
The nucleotide-binding oligomerization domain (NOD)-like receptor (NLR) protein 3 (NLRP3) inflammasome pathway is believed to mediate chronic inflammation in diabetic retinopathy (DR); however, its impact on the progression of DR remains to be elucidated. Therefore, the primary aim of this pilot study was to determine whether systemic inflammasome biomarkers interleukin (IL)-1β and IL-18 can be used to predict DR progression. DR screening results were analyzed against weight, level of glycated hemoglobin (HbA1c), and plasma levels of inflammasome biomarkers (IL-1β and IL-18), as well as general inflammation markers (C-reactive protein (CRP), IL-6, IL-8, tumor necrosis factor-alpha (TNF-α), and vascular endothelial growth factor (VEGF)) in patients with type 2 diabetes at baseline and 1 year post-bariatric surgery. Cross-sectional analysis demonstrated that weight, HbA1c, CRP, and IL-18 did not correlate with DR severity. The progressed group showed a higher relative change in IL-18 and CRP levels compared to the stable and regressed groups. Furthermore, relative changes in plasma CRP levels correlated with those of IL-18. Although further validation with larger cohorts is necessary, this pilot study supports the hypothesis that systemic inflammasome activation is associated with DR progression.